"Properly speaking, ideology is not fallacy" : Felipe Martínez Marzoa declines the "tarte à la crème du marxisme" - Jiménez Heffernan, Julián (Tropelías: Review of Literary Theory and Comparative Literature, 2023)
The recent re-edition of Felipe Martínez Marzoa’s La Filosofía de El Capital (2018), originally published in 1982, can be taken as an indirect invitation to reconsider the exact meaning of a term, “ideology”, which has played a crucial role in modern literary theory. Marzoa’s radical thesis, according to which “properly speaking, ideology is not fallacy”, runs against both Marx’s and Engels’s original position and its reinterpretation by materialist thinkers like Adorno, Althusser, Habermas, Ricoeur, Badiou, Zizek or Derrida. Still, because Marzoa’s thesis is formulated in a Heideggerian jargon whereby ideology is to structure what metaphysics is to ontology, the true grasp of this thesis requires our theoretical elaboration to conform to the terms originally stipulated by the German thinker. The thesis, however, happens to be contaminated, in the last instance, by markedly idealist, if not romantic, undertones. Marzoa’s resistance to accept the Marxian terms of this problematic could well be a symptom of a broader, characteristically Spanish, resistance to think ideology.